A computer simulation of sonar signal propagation by ray method - Свинчук, О. В.; Євтушенко, А. М.; Пуха, Г. С.; Пироговська, Т. В. (Інститут проблем реєстрації інформації НАН України, 2022)
Modeling of sound rays is an important task in underwater acoustics, because solving this problem helps to solve many practical problems of modern sonar systems, by increasing the informative characteristics of signal propagation for both military and civilian research in the seas and oceans. Today, there are many different mathematical models based on different approaches. The most well-known models of ray tracing are the Bellhop and Traceo models, which calculate the sound field in a horizontal inhomogeneous water environment by tracking a Gaussian ray. This paper describes a number of models based on the classical theory of rays, which is easy to implement and is based on solving simple differential equations that provide the necessary information about the trajectory of rays in any direction and location of the radiation source. To compare these models and determine the accuracy of each of them, a software product was created to model the propagation of sonar signals in the marine environment to assess their disadvantages and advantages for further development of software tools for analysis and study of sonar signals in a multilayer marine environment. The developed solution consists of a main program and three class libraries, each of which implements a set of methods for constructing a ray trajectory according to an algorithm from the Traceo model, a geometric model and a linear model. To simulate the propagation of sonar signals in the marine environment, various speed velocity profiles were recorded in the program. High reliability of modeling of propagation of hydroacoustic signals of linear model allows compare accuracy of construction of a trajectory of beams to other offered models. The development of new software products based on previously developed radiation theory, and the improvement of existing software products will allow to more accurately assess the various parameters of the marine environment and solve more complex problems of ray tracing.